Holocene vegetation history in the Northern Vosges Mountains (NE France): Palynological, geochemical and sedimentological data. (June 2020) - Gouriveau, Emilie; Ruffaldi, Pascale; Duchamp, Loïc; Robin, Vincent; Schnitzler, Annik; Walter-Simonnet, Anne-Véronique
Palynological data from the Northern Vosges Mountains (NVM) are very rare, unlike for the Southern and Central Vosges Mountains, where the past vegetation history is relatively well known. As a consequence, the beginning of human activities has never been clearly identified and dated in the NVM. In order to reconstruct the evolution of vegetation in this region, multiproxy studies (pollen, non-pollen palynomorphs, sedimentological and geochemical analyses) were conducted in two peatlands. Overall, the results, extending from about 9500 cal. BP to recent times, show a classical vegetation succession with local particularities resulting from human activities. In the La Horn peatland, a strong human impact related to pastoralism is attested from the late Bronze Age onwards. The second phase of human occupation, mainly characterized by crop cultures, begins during the Hallstatt period. The geochemical results (x-ray fluorescence) also highlight the presence of metallic elements, which, combined with significant quantities of carbonized particles, point to potential metal working. In the Kobert-Haut peatland, human occupation began much later (1500 cal. BP), but lasted from the Gallo-Roman period to the beginning of the Modern Period. Unlike for the vegetation history of the rest of the Vosges, Pinus remains a prevailing taxon throughout the Holocene in the NVM. Another particularity is the early establishment of Picea, long before the 18th to 19th century plantations.